Traumatic Experiences in Eka Kurniawan's Novel Seperti Dendam, Rindu Harus Dibayar Tuntas - Endang Sartika (POETIKA, 2020)
The emergence of trauma study with the publication of Cathy Caruth's Unclaimed Experience: Trauma, Narrative, and History have gained significant interest in analyzing traumatic experiences in literary works. Literary trauma is seen as the media and alternative to read the wound and trauma through narration and fiction in the form of an anxiety plot. This study aims to analyze the traumatic experiences in Eka Kurniawan's novel entitled Seperti Dendam, Rindu Harus Dibayar Tuntas. This research is descriptive qualitative in nature. The objects of this research are the traumatic events and experiences in Kurniawan's novel. The data were collected by note taking and highlighting the relevant traumatic event and analyzed using the concept of trauma and memory of Cathy Caruth. The result shows that the characters in this novel respond to trauma differently such as having intrusive thoughts, re-experiencing the trauma through flashbacks and dreams, avoidance, and having negative feelings and moods. The novel shows that the socio-cultural environment can become the greatest source of trauma as well as offer the healing process for the traumatized through compassion and understanding. The characters' traumatic experience is narrated by the unknown godlike narrator. Through the portrayal of the characters, Kurniawan reveals how pain, suffering, and traumatic experiences lead the characters to gain high self-esteem, self-knowledge, and philosophical understanding of social reality.